MUSICAL INCUNABULA IN LITHUANIA’S LIBRARIES - STONYTĖ, ŽIVILĖ (Knygotyra, 2012)
This article presents four musical incunabula currently kept in Lithuanian libraries. Three of them, found in the Lithuanian National Martynas Mažvydas Library, will be discussed in detail, assessing their significance in music printing history. Based on musical incunabula classification, the publications shall be discussed according to the nature of the printed musical material, looking at whether the publications contain: 1) printed notes and staves (Graduale Romanum, Venice: Luc’Antonio Giunta, 1499/1500), 2) only printed notes or only staves (Jean Gerson Collectorium super Magnificat, Esslingen: Conrad Fyner, 1473), and 3) blank spaces on the page left for the insertion of manuscript music (Missale Basiliense, Basel: Nicolaus Kessler, 1485). A descriptive publication research method is used in the article which reveals the evolution of note printing and shows the variety of possibilities in 15th-century music printing. It also analyses the particularities of genre and repertoire in liturgical musical incunabula, discussing their use and marks of ownership.